Analysis of Factors Affecting Customer Decision to Saving at Bank Sharia Indonesia, Palopo City - Puspa Indah Mulfi (Program Studi Perbankan Syariah, IAIN Palopo, 2022)
The results of the study show that: (1) knowledge (X1) has a positive and significant effect on customers' decisions to save at BSI because the tcount is 2.562 > ttable 1.664 and sig. 0.012 <0.05 or in other words H0 is rejected H1 is accepted. (2) Service (X2) has a positive and significant effect on customers' decisions to save at BSI because the tcount is 2.150 > ttable 1.664 and sig. 0.035 <0.05 or in other words H0 is rejected H1 is accepted. (3) Promotion (X3) has a positive and significant effect on customers' decisions to save at BSI because the tcount is 2.105 > ttable 1.664 and sig. 0.038 <0.05 or in other words H0 is rejected H1 is accepted. There is an influence between the variables X1, X2 and X3 on Y which can be seen from the results of the coefficient of determination test which shows an Adjusted Square value of 0.178 equivalent to 17.8%. This means that 17.8% of customers' decisions to save at BSI are influenced by knowledge, service and promotion. Then 82.2% was influenced by other factors not explained in the study.